Short-Term Grazing Exclusion Alters Soil Bacterial Co-occurrence Patterns Rather Than Community Diversity or Composition in Temperate Grasslands - Wang, Fangfang; Li, Zongming; Fu, Bojie; Lü, Yihe; Liu, Guoping; Wang, Dongbo; Wu, Xing (Frontiers in Microbiology, 2022)
Grazing exclusion is one of the most common practices for degraded grassland restoration worldwide. Soil microorganisms are critical components in soil and play important roles in maintaining grassland ecosystem functions. However, the changes of soil bacterial community characteristics during grazing exclusion for different types of grassland remain unclear. In this study, the soil bacterial community diversity and composition, as well as the co-occurrence patterns were investigated and compared between grazing exclusion (4 years) and the paired adjacent grazing sites for three types of temperate grasslands (desert steppe, typical steppe and meadow steppe) in the Hulunbuir grassland of Inner Mongolia. Our results showed that short-term grazing exclusion decreased the complexity and connectivity of bacterial co-occurrence patterns while increased the network modules in three types of temperate grasslands. The effects of grazing exclusion on soil bacterial α-diversity and composition were not significant in typical steppe and meadow steppe. However, short-term grazing exclusion significantly altered the community composition in desert steppe, indicating that the soil bacteria communities in desert steppe could response faster than those in other two types of steppes. In addition, the composition of bacterial community is predominantly affected by soil chemical properties, such as soil total carbon (STC) and pH, instead of spatial distance. These results indicated that short-term grazing exclusion altered the soil bacterial co-occurrence patterns rather than community diversity or composition in three types of temperate grasslands. Moreover, our study suggested that soil bacterial co-occurrence patterns were more sensitive to grazing exclusion and the restoration of soil bacterial community might need a long term (> 4 years) in our study area.